The Effect of Adding Sappan Wood Powder and Potassium Sorbate on The Quality of Borneo Coconut Soy Sauce - Maryam, Andi; Saskia, Neti; Andiyono, Andiyono (FoodTech: Jurnal Teknologi Pangan, 2024)
Borneo Coconut Soy Sauce has problems with shelf life, namely on the fifth day the soy sauce has experienced a decline in quality, so the problem faced is a short shelf life. So the synthetic preservative potassium sorbate and natural sappan wood preservative were added to extend the shelf life of the product. Potassium sorbate is used to prevent the growth of bacteria, fungi and mold. Sappan wood contains active antimicrobial and antioxidant substances which can inhibit and reduce the number of microbes in food, so that sappan wood can extend its shelf life. This research aims to determine the effect of adding potassium sorbate and sappan sawdust on sugar content, Total Plate Number (ALT), protein content, and organoleptic tests of Borneo coconut soy sauce. This research used a non-factorial Randomized Block Design (RAK) method with 6 treatment, namely K0S2, K1S2, K1S1, K2S0, K2S2, and K2S1. The highest average sugar content test results were in the K1S1 treatment, namely 52.60% and the lowest in the K2S0 treatment, namely 41.66%. The ALT test results showed that samples K0S2, K1S2, K1S1, K2S0, and K2S2 were declared negative for being contaminated with bacteria, while sample K2S1 was positive for being contaminated with bacteria but did not exceed the maximum limit set by BPOM and BSN, because the ALT value of sample K2S1 was 1 x 10 ². The protein content test results had the highest average value in the K2S2 treatment, namely 3.62% and the lowest in the K2S0 treatment, namely 2.95%. Based on the organoleptic test, the highest average value for taste, color and aroma was the same, namely in the K0S2 treatment, while the lowest average value for taste was in the K1S1 treatment, for color, namely in the K2S0 treatment, and for aroma, namely in the K2S2 treatment.